Analysis of the Effectiveness of the Omnibus Method in Drafting Laws to Realize Business Licensing Law Reform in Indonesia - Setiadi, Elen; Redi, Ahmad (Greenation Publisher & Yayasan Global Resarch National, 2025)
The omnibus method is a new approach in the formation of legislation in Indonesia which aims to simplify regulations and overcome overlapping legal rules. This study aims to analyze the effectiveness of the omnibus method in drafting laws as a means of realizing legal reform of business licensing in Indonesia. Through normative studies and analysis of the Job Creation Law as an example of the application of the omnibus method, this study found that it can accelerate regulatory harmonization and provide legal certainty for business actors. However, its effectiveness has encountered challenges in public participation, transparency, and potential violations of the principles of good legal regulation formation. Therefore, it is necessary to strengthen the legislative mechanism so that the omnibus method can truly function as an instrument of sustainable legal reform.